2017
DOI: 10.3177/jnsv.63.167
|View full text |Cite
|
Sign up to set email alerts
|

Perceived 6-<i>n</i>-Propylthiouracil (PROP) Bitterness Is Associated with Dietary Sodium Intake in Female Japanese College Students

Abstract: Summary Despite the negative health consequences of a high sodium consumption, humans consume well above the recommended levels. This study examines whether or not the dietary intake of sodium was affected by individual variation of the perceived bitterness of 6-n-propylthiouracil (PROP), and examines the relationship between the perceived bitterness of PROP and the preferred NaCl concentration of broth. Female students (20-22 y old) were recruited from the university community. Genotypes of A49P and I296V pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In our previous systematic review of adolescents' taste perception and food choices, we found that perceived bitterness in cruciferous vegetables (i.e., broccoli, cabbage, Brussels sprouts and cauliflower) was negatively associated with intake and preferences and positively associated with energy intake. However, this was not consistent due to variations in the taste assessment among the studies (12); likewise in adults (19)(20)(21). This inconsistency may be due to variations in the taste assessment where studies have tested this relationship using liquid solutions of taste samples and/or limited individual food items as references to evaluate the influence of individuals' taste perceptions and/or preferences on selected dietary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous systematic review of adolescents' taste perception and food choices, we found that perceived bitterness in cruciferous vegetables (i.e., broccoli, cabbage, Brussels sprouts and cauliflower) was negatively associated with intake and preferences and positively associated with energy intake. However, this was not consistent due to variations in the taste assessment among the studies (12); likewise in adults (19)(20)(21). This inconsistency may be due to variations in the taste assessment where studies have tested this relationship using liquid solutions of taste samples and/or limited individual food items as references to evaluate the influence of individuals' taste perceptions and/or preferences on selected dietary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent sources of vitamin E are edible vegetable oils, such as those of corn, olive, palm, rice bran, and peanut [ 47 ]. Thus, the genotype could be associated with fat-soluble nutrients consumption [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited evidences only exist surrounding bitterness genetic variation and saltiness and sodium intake [ 45 46 47 48 ]. However, a study with young Japanese females suggested that the genetic variation in TAS2R38 contributed to increased sodium intake [ 48 ]. A study with small number of Iraqi males investigated the PTC phenotype and blood pressure marker.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have failed to establish a relationship between sensory properties and actual salt consumption (Drewnowski et al, 1996;Kim et al, 2017;Pilic & Mavrommatis, 2018;Inoue et al, 2017;Kubota et al, 2018). The lack of consensus may be due to insensitivity in methods used to assess sodium intake (Mattes, 1997) or in the variations of methods chosen to evaluate the salt sensitivity phenotype as well as their measurement properties.…”
Section: Introductionmentioning
confidence: 99%